Validity and reliability of the Turkish version of the Optimality Index-US (OI-US) to assess maternity care outcomes. Issue 12 (December 2015) - Yucel, Cigdem; Taskin, Lale; Low, Lisa Kane
Abstract: Background: although obstetrical interventions are used commonly in Turkey, there is no standardized evidence-based assessment tool to evaluate maternity care outcomes. The Optimality Index-US (OI-US) is an evidence-based tool that was developed for the purpose of measuring aggregate perinatal care processes and outcomes against an optimal or best possible standard. This index has been validated and used in Netherlands, USA and UK until now. Objective: the objective of this study was to adapt the OI-US to assess maternity care outcomes in Turkey. Design: translation and back translation were used to develop the Optimality Index-Turkey (OI-TR) version. To evaluate the content validity of the OI-TR, an expert panel group ( n =10) reviewed the items and evidence-based quality of the OI-TR for application in Turkey. Following the content validity process, the OI-TR was used to assess 150 healthy and 150 high-risk pregnant women who gave birth at a high volume, urban maternity hospital in Turkey. The scores between the two groups were compared to assess the discriminant validity of the OI-TR. The percentage of agreement between two raters and the Kappa statistic were calculated to evaluate the reliability. Findings: content validity was established for the OI-TR by an expert group. Discriminant validity was confirmed by comparing the OI scores of healthy pregnant women (mean OI score=77.65%) and those of high-risk pregnant women (mean OI score=78.60%). The percentage of agreement between the two raters was 96.19, and inter-rater agreement was provided for each item in the OI-TR. Conclusion: OI-TR is a valid and reliable tool that can be used to assess maternity care outcomes in Turkey. The results of this study indicate that although the risk statuses of the women differed, the type of care they received was essentially the same, as measured by the OI-TR. Care was not individualised based on risk and for a majority of items was inconsistent with evidence based practice, which is not optimal. Implications for practice: use of the OI-TR will help to provide a standardized way to assess maternity care process and outcomes of maternity care in Turkey which can inform future research aimed at improving maternity care outcomes.